SISTEM INFORMASI PENJUALAN OBAT BERBASIS WEB PADA APOTEK KONDANG WARAS DEPOK - Sri Wasiyanti; Roholesi Talaohu (Paradigma, 2016)
Website of the forerunner of the development of information technology in the field of the internet. With the sophistication of the software and current hardwere, allows to create a website that is far more interesting and interactive. One of the websites that have a place big on the internet is a website in the field of e-commerce or trade online. With e-commerce, people no longer need to search for the required goods directly or come to the stores that sell the item. With e-commerce is also a registered user or subscriber only needs to access a site that provides trade services online without having to wait or queue up struggled in a store or outlet, that is what makes e-commerce as a reference in the era of free trade. Where e-commerce makes it easy for any customer in fulfilling the desires of clothing and food. The existence of the website community is easier to get information about trade in search, as it can be accessed anywhere and at anytime. Therefore to expand the scope of marketing drugs at the pharmacy Kondang Waras, the author makes a website selling drugs that adjust to the needs that exist in society with attention to procedures design of a website in order to be easily accessible to a broad audience.Key Word: Program, Design, Drug Sales, Web.